2022
DOI: 10.54905/disssi/v26i129/ms505e2523
|View full text |Cite
|
Sign up to set email alerts
|

The knowledge of Schizophrenia among health- related students in Umm Al-Qura University: A cross sectional survey

Abstract: Background: Schizophrenia is a mental psychotic disorder where the patient may experience hallucinations or disorganized speech with the likely correlation with negative symptoms. This study aimed to estimate the knowledge, awareness and attitude of schizophrenia among health-related students at Umm Al-Qura University in Saudi Arabia. Methods: A cross sectional study was conducted among interns and undergraduate students from different health related specialties at Umm Al-Qura University. Data is collected by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…This gradual increase could be due to partly genetic and environmental factors. Colorectal Cancer (CRC) also known as colon cancer, bowel cancer or rectal cancer and cancer originate from the colon and some part of rectum (Bakry et al, 2021).…”
Section: Medical Sciencementioning
confidence: 99%
“…This gradual increase could be due to partly genetic and environmental factors. Colorectal Cancer (CRC) also known as colon cancer, bowel cancer or rectal cancer and cancer originate from the colon and some part of rectum (Bakry et al, 2021).…”
Section: Medical Sciencementioning
confidence: 99%
“…This progressive growth might be attributed to a combination of hereditary and environmental causes. Colorectal cancer (CRC), commonly known as colon cancer, bowel cancer, or rectal cancer, is a kind of cancer that begins in the colon and extends into the rectum (Bakry et al, 2021). The incidence of colorectal cancer is increasing in Saudi Arabia, and many studies have identified low fiber diet intake, high fat, spicy and oily foods, more red meat consumption in their regular diets, non-adherence to screening programs, other lifestyle factors, and ignorance as risk factors for CRC.…”
Section: Introductionmentioning
confidence: 99%